Analiza nawyków i zachowań związanych higieną jamy ustnej = Analysis of oral hygiene-related habits and behaviours - Kozłowski, Piotr; Streit, Dominika; Kozłowska, Magdalena; Cuch, Barbara (Journal of Education, Health and Sport, 2015)
Kozłowska Magdalena, Streit Dominika, Kozłowski Piotr, Cuch Barbara. Analiza nawyków i zachowań związanych higieną jamy ustnej = Analysis of oral hygiene-related habits and behaviours. Journal of Education, Health and Sport. 2015;5(9):95-101. ISSN 2391-8306. DOI10.5281/zenodo.29915 http://dx.doi.org/10.5281/zenodo.29915 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A95-101 https://pbn.nauka.gov.pl/works/615869 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 24.08.2015. ANALIZA NAWYKÓW I ZACHOWAŃ ZWIĄZANYCH HIGIENĄ JAMY USTNEJ. Analysis of oral hygiene-related habits and behaviours Magdalena Kozłowska1, Dominika Streit2, Piotr Kozłowski3, Barbara Cuch3 1Katedra i Klinika Neurologii, UM w Lublinie 2Uniwersytet Medyczny w Lublinie 3Katedra i Zakład Anatomii Prawidłowej Człowieka, UM w Lublinie Uniwersytet Medyczny w Lublinie ul. Aleje Racławickie 1, 20-093 Lublin e-mail: piotr7176@gmail.com Abstrakt: Celem pracy była ocena nawyków i zachowań związanych z higieną jamy ustnej. Badaniem objęto 120 osób. W grupie badanej kobiety stanowiły 78,3% ankietowanych, natomiast mężczyźni 21,7%. Wiek ankietowanych zawierał się w przedziale od 18 do 65 lat. Badanie przeprowadzono w styczniu 2015 roku metodą wywiadu standaryzowanego. Narzędziem badawczym, którym posłużono się do zebrania danych, był autorski kwestionariusz, który zawierał 21 pytań. Przeprowadzono analizę statystyczną z wykorzystaniem testu chi- kwadrat. Wszystkie wartości w których p<0,05 uznano za istotne statystycznie. Niespełna połowa, bo 45,8% ankietowanych myło zęby rano, natomiast wieczorem przed pójściem spać zęby myło już 95% respondentów. Największa część ankietowanych myła zęby przez ok 2 min (43,3%). Podczas codziennej higieny jamy ustnej język i przedsionek jamy ustnej myło 71,7% respondentów. Odsetek osób myjących zęby po zjedzeniu słodkiego posiłku wynosił 36,7%, natomiast jamę ustną po spożyciu posiłku o niskim pH wodą płukało jedynie 25,8% respondentów. Ponad połowa (60%) osób niemyjących zębów po słodkim posiłku miała od 1 do 5 wypełnień, odpowiednio w grupie respondentów posiadających od 6 do 10 wypełnień w zębach 64% stanowiły osoby nie myjące zębów po zjedzeniu słodkich posiłków. Płyny do płukania jamy ustnej używało 50,8% respondentów. Nitka dentystyczna używana była przez 49,2% ankietowanych. Ponad jedna trzecia ankietowanych (37,5%) chodziła do dentysty raz na pół roku. Najczęstszą przyczyną (67,5%) wizyty u stomatologa była wizyta kontrolna, ból zęba był przyczyną jedynie 15% wizyt u dentysty. Słowa kluczowe: higiena jamy ustnej, nieprawidłowe nawyki, mycie zębów. Abstract The aim of the study was to evaluate habits and behaviours related to oral hygiene. The study involved 120 people. In the study group women accounted for 78.3%, while 21.7% of the respondents were men. The age of the respondents ranged from 18 to 65. the study was conducted in January 2015 incorporating a standardized interview research method. The research tool used was a questionnaire that included 21 questions. Statistical analysis was performed using chi-square test. All values with p<0.05 were considered statistically significant. Less than a half (45.8%) of the respondents brushed their teeth in the morning. However, as many as 95% brushed their teeth before going to bed. The largest group of the surveyed (43.3%) brushed their teeth for about 2 minutes. 71.7% claimed to clean their tongue and the vestibule on a daily basis. The percentage of people who brushed their teeth after eating a sugar-contains meal amounted to 36.7%. Only 25.8% of the respondents rinsed their mouth with water after eating a meal with a low pH. More than a half (60%) of those who did not brush their teeth after a sugar-containing meal had from 1 to 5 fillings. Within the group with 6 to 10 fillings, 64% were those who who did not brush their teeth after eating a sugar-containing meal. Liquid mouthwash was used by 50.8% of the respondents and dental floss was used by 49.2%. Over one third (37.5%) of the respondents claimed to visit a dentist every six months. Most cases were routine check-ups, and only 15% of all the appointments were toothache-related. Key words: oral hygiene, bad habits, teeth brushing.